Constructive Technologies With Bamboo. A Sustainable Responsefor Housing in the Huasteca Area of San Luis Potosí - Arista González, Gerardo Javier (Centro Universitario de Arte, Arquitectura y Diseño, 2017)
The house has been one of the objects of greater interest for the research, as well as it is also for  the design of technical and architectural solutions of the habitable spaces. In particular, social housing is a matter of high priority for the country, given the high percentage of the population that does not have decent housing. The bamboo, known as “vegetable steel”, which is produced in multiple regions of Latin America with a humid warm climate, represents an input with characteristics suitable for building that  make it a natural resource susceptible to be used as a material for low-cost housing construction. To generate sustainable architectural proto-types using bamboo as a constructive element, constitutes the main objective of this paper, which aims to place in value the house with the qualification of sustainable, not only because of the saving of transport and the energy of industrialized inputs to the communities, but from its technical-architectonic conception and considering how to reach the probable auto-construction of the houses by means of training and technical assistance to future users.